Strategies and obstacles on the path for Type 1 diabetes therapies - von Herrath, Matthias (Henry Stewart Talks, 2019)
Prevalence, burden and causes of type 1 diabetes, Diabetes stages and intervention options, A possible proinsulin processing issue, Vision for type 1 diabetes treatment, Obstacles in bringing therapies to the clinic